The significance of tax risk for Polish companies based on the findings of an empirical study - Witczak, Izabela (Research Papers in Economics and Finance, 2024)
Discussion of the problem of tax risk based on the empirical study. The paper explains the main aspects of tax risk, tax risk areas and its assessment. Critical analysis of existing literature and tax laws. Conclusions are formulated using a deductive method in the framework of tax theory and based on the analysis of tax laws and the author’s survey into the problem of tax risk conducted in the Wielkopolskie voivodeship in 2020. The survey results show that managers are increasingly aware of the tax risks associated with the activities of their companies and the industries in which they operate. They also indicate that, regardless of their size, companies should use tax risk management systems aligned with their tax strategies and managed by qualified staff. The article contributes to the analysis of tax risk.